(untitled) (Al-Academy, 2025)
The current research aims to explore and highlight the technical and artistic capabilities of the Mental Canvas program to enrich research approaches through its technical and artistic features. It seeks to establish a set of educational standards for designing digital illustrations to produce a children’s booklet, emphasize the significance of the Mental Canvas program, and enhance the knowledge base related to modern digital art programs specializing in interactive 3D illustrations. The results of this study could contribute to identifying the importance of using Mental Canvas and its tools in teaching and enhancing their utilization through the application of recommendations proposed by the researcher. Additionally, the study involves designing a prototype of an interactive 3D booklet for children using Mental Canvas, utilizing illustrative designs, and examining the role of interactive 3D illustrations for children in instilling values, customs, and traditions in Saudi children. The researcher used an observation card as a research tool and adopted the descriptive-analytical method for the study. The research findings revealed several results, the most notable of which include: The technical capabilities for designing interactive digital illustrations using Mental Canvas to produce an interactive booklet for children with a Saudi character received a high level of responsiveness from the sample group. The artistic capabilities for designing interactive digital illustrations using Mental Canvas for the same purpose were rated with a moderate level of responsiveness by the sample group. The researcher proposed several recommendations, including: 1. Encouraging methods and approaches that aim to uncover new avenues for developing educational curricula. 2. Urging researchers and artists to integrate 3D illustrations with 2D designs. 3. Encouraging educators to leverage the technical capabilities of the Mental Canvas program. 4. Including illustrative designs as part of teaching methodologies. 5. Promoting collaboration between teachers and researchers to better understand the importance of teachers’ skill development in using Mental Canvas and other interactive digital drawing programs in education. 6. Conducting studies on the behavioral impact of instilling Saudi customs and traditions in children through interactive digital drawing programs. 7. Investigating the effect of using interactive digital drawing programs in education on the teacher-student relationship. 8. Conducting similar studies in other countries for comparative analysis